The Causal Relationship between Economic Growth, Banking Sector Development and Stock Market Development in Selected Middle-East and North African Countries - Vahid Puryan (International Journal of Economics and Financial Issues, 2017)
Economic growth is the major indicator of government's performances; hence, economists always trying to help policy-makers in this field through accurate recognizing of dynamisms and factor affecting this indicator. On the other hand, financial and monetary markets play a vital role in directing existing funds in economy toward producing and industrial sectors to improve economic growth. In this regard, some economists believe that expanded financial markets are driving force of economic growth is countries. This research has investigated the causal relationship between economic growth, banking sector development, and stock market development in selected MENA countries during 1988-2012. To measure development of banking and stock market sectors, 4 indexes are introduced that are converting to two general indexes for each sector using decomposition method for principle components. To test causal relationship between economic growths, banking sector and stock market development, Granger causality test based on vector auto regression of error correction has been applied. According to the results of this study, there is a one-way causal relationship from banking sector development toward economic growth, a mutual causal relationship between stock market development and economic growth, and a one-way causal relationship from banking sector development toward stock market. Stock market development has a long-run positive effect on economic growth.